Cardiac function of colorectal cancer mice is remotely controlled by gut microbiota: regulating serum metabolites and myocardial cytokines - Zhan-Kui Gao; Chao-Yuan Fan; Bo-Wen Zhang; Jia-Xin Geng; Xing Han; Dan-Qi Xu; Muhammad Arshad; Hao-Xuan Sun; Jiong-Yi Li; Xiangyuan Jin; Xiao-Qin Mu (Animal Microbiome)
Abstract Several studies have indicated that the dysregulation of microbial metabolites and the inflammatory environment resulting from microbial dysbiosis may contribute to the occurrence and progression of cardiovascular diseases. Therefore, restoring the disordered gut microbiota in patients with colorectal cancer by fecal microbiota transplantation (FMT) has the potential to reduce the incidence of cardiac disease. In this study, we identified cardiac dysfunction in azomethane and dextran sodium sulfate-induced colorectal cancer mice. Intestinal microbes from healthy mice were transferred to colorectal cancer mice, which vastly reversed the disorder of the gut microbiota and effectively alleviated cardiac dysfunction. Moreover, FMT regulated the expression of serum metabolites such as uridine triphosphate (UTP), tiamulin, andrographolide, and N-Acetyl-D-glucosamine, as well as cytokines like TGF-β, IRF5, and β-MHC in the heart. These findings uncover that the disturbed gut microbiota causes cardiac dysfunction in colorectal cancer mice by modulating the expression of serum metabolites and cytokines, which could be alleviated by treatment with FMT.